Excreção de sódio e taxa de filtração glomerular em afrodescendentes de Alcântara-MA - SANTOS, Elisângela Milhomem dos (2017)
Introduction: Excessive salt consumption has been observed in most countries over the last years, ranging from nine to 12 grams per person per day, above the limit recommended by the World Health Organization which is five grams at the most. Currently, high sodium intake has been considered a major risk factor for development of diseases. The 24-hour urinary sodium excretion is considered the gold standard method for evaluation of sodium consumption; however, difficulties associated with accuracy of urine collections may interfere with the results. Estimation of sodium intake by spot urine samples, at population level, has been increasingly used as a suitable and inexpensive alternative. Methods: Cross-sectional study with 1,211 African descendants from Alcântara, Maranhão. Demographic, lifestyle, clinical and laboratory data were evaluated. The urinary excretion estimation of sodium and the estimated glomerular filtration rate (eGFR) were obtained using the Kawasaki and the CKDEPI equations, respectively. In order to identify variables related to sodium excretion, the multivariate linear regression model was used and the variables with p value < 0.20 were included in the analysis. A multivariate linear regression model was used to determine the relationship between eGFR and sodium excretion. A significance level of 5% was used and the data were analyzed using the STATA 14.0 software. Results: Most individuals were women (52.8%) with a mean age of 37.5 ± 11.7 years. The prevalence of hypertension was 21.3%. The mean excretion of sodium was 204.6 ± 15.3 mmol/d and the eGFR was 111.8 ± 15.3 mL / min / 1.73 m². Hypertensive individuals showed higher sodium excretion (217.9 ± 90.1 mmol / d vs 199.2 ± 83.0 mmol \ d; p = 0.002). After the adjusted analysis, the waist circumference (PR = 1.16), triglycerides (RP = 1.13), systolic blood pressure (RP = 1.19) and eGFR (RP = 1.24) remained related with urinary sodium excretion. According to the multivariate linear regression, the eGFR was correlated independently with sodium excretion (β = 0.11, p <0.001), age (β = -0.67, p <0.001), female gender (β = -0.20, p <0.001) and BMI (β=-0.09; p <0.001). Conclusion: Urinary excretion of sodium was high in spot urine sample. Furthermore, association with waist circumference, triglycerides, systolic blood pressure and eGFR was observed. The eGFR was negatively correlated with age, female gender and body mass index. Conversely, there was a positive correlation between eGFR and urinary sodium excretion.